ICRISAT's Landscape-based Fertilizer Advisory Tool to Benefit Over 15,000 Farmers in Ethiopia - Desta, Gizaw (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Hawassa, Sidama Regional State: The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT-Ethiopia) conducted a successful two-day workshop from 12 to 13 June 2024. The workshop aimed at piloting and scaling a landscape-based fertilizer advisory system. This initiative, part of the CGIAR Excellence in Agronomy program, is expected to benefit over 15,000 farmers this season.